Difference in Defecation Desire Between Patients With and Without Chronic Constipation: A Large-Scale Internet Survey. Issue 9 (1st September 2020) - Ohkubo, Hidenori; Takatsu, Tomohiro; Yoshihara, Tsutomu; Misawa, Noboru; Ashikari, Keiichi; Fuyuki, Akiko; Matsuura, Tetsuya; Higurashi, Takuma; Yamamoto, Kouji; Matsumoto, Heido; Odaka, Takeo; Lembo, Anthony J.; et al.
Abstract : INTRODUCTION: Defecation desire (DD) is an important physiological component of normal defecation. However, knowledge of DD in the general population and in individuals with chronic constipation (CC) is lacking. We aimed to assess the prevalence of DD in the general population and individuals with CC and to understand the impact of treatment on DD among individuals with CC. METHODS: We conducted an online questionnaire survey targeting the Japanese general population in 2019. DD was reported as never, rarely, usually, or always. Individuals who self-reported constipation and met the Rome IV criteria for functional constipation but did not for irritable bowel syndrome were included in the CC group, while the same number of age-/sex-matched controls who met neither functional constipation nor irritable bowel syndrome criteria was included in the non-CC group. Individuals who reported DD as rarely or never were defined as having loss of DD (LODD). RESULTS: Of the 20, 986 participants, 2, 587 were included in the CC group (12.3%). LODD was significantly higher in the CC individuals than in the non-CC controls (57.4% vs 8.3%, respectively, P < 0.001, odds ratio 14.84 [95% confidence interval 12.65–17.42]). Satisfaction with treatment for constipation was lower in individuals with persistent LODD (25.9%) compared with those with improved LODD (56.5%) on treatment ( P < 0.001, odds ratio 2.48 [1.39–4.43]). DISCUSSION: LODD is common in CC and is associated with decreased satisfaction to treatment. Greater attention should be paid to DD when treating patients with CC.